A CONSTRUÇAO CULTURAL DA IDENTIDADE DO/A PEDAGOGO/A PELO CURRÍCULO - OLIVEIRA, Kelly Almeida de (2011)
It s a paper about the process of the identity s cultural construction of the pedagogue who is graduated in the Federal University of Maranhão - UFMA. Our goal is analyzing how occurs this process in the formation context through the curriculum. Therefore, our main question is discovering how can the curriculum form identities? In order to reach the answer we propose to understand how the process of the identity construction is seen by several sciences, and check back the history of the curriculum and the curricular theories to relate them to the pedagogue s identities formation since the beginning of the course in 1939 in Brazil and until the first decade of the XXI century in Maranhão. Moreover, we also search to identify in the national legislation and in the pedagogical politic project of this course at Federal University of Maranhão how the pedagogue s identity formation is established taking into account its occupation in the labor market from the official discourse, the power and the ideology which it brings. Furthermore, we highlight the participation of the people involved in this process through the teachers contribution in the students identity construction and also through the cultural and scientific elements acquired by them in their own identity formation as pedagogues. All the job was based on questionnaires with the students from two colleges of cities of São Luís e Imperatriz in the second, seventh and eighth period who expressed their feelings about the their formation connecting it to the cultural construction of their identities, and also based on some interviews with the teachers and coordinators of the course identifying their point of view about the commitment of their students with their identity construction. Besides these people, we also asked the opinion of some pedagogues who were graduated at the Federal University of Maranhão. Eight pedagogues were chosen to be interviewed; four from each college and the professors Maria Alice Melo and Lílian Saldanha about their participation in the Curricular Reformulation of 2001 in Maranhão. In order to compound our theoretical knowledge we studied about curriculum, identity and Pedagogy course which are our main categories. This study was possible due to the contributions of some authors such as Moreira (1990) and Apple (2006) about curriculum; Hall (2009) and Woodward (2009) about identities and Soares (1984), Brzezinski (1996) and Silva (2006) about the pedagogy course. As subcategories we listed: ideology, in the Apple s conception (2006); power, which was worked by Foucault (1979); culture, in the Freire s point of view (2001); professional identity, worked by Dubar (2005; 2009); discourses, under Foucault analysis (1996); pedagogical practices and theories, both interpreted by Tardiff (2000, 2002). We describe and analyze the process of cultural construction of identity / the teacher / a. By historicizing curriculum category we find that each structure has a curriculum intended to be formed professional. Legislation found in the discourses that determine identities. We note the involvement of teachers in this process, they pointed out in the elements that must be present in the training of undergraduates and the responses of undergraduates and graduates of the course we understand how they appropriate the elements posed by teachers and how they negotiate their identities. It was possible to identify the moments take part of the identity cultural construction in order to confirm our idea that pedagogue s identity is, above all, a cultural social historic aspect supported by the curricular organization of the course.